Advanced exergy analysis of vapor compression systems using low-GWP refrigerants and variable-frequency compressor - Rahul Deharkar; Parth Prajapati; Bansi D. Raja; Vivek K. Patel (International Journal of Thermofluids)
This study investigates the performance of a vapor compression refrigeration system equipped with three different expansion devices (capillary tube, thermostatic valve and an electronic valve) along with a variable-frequency compressor. The primary objective is to optimize system efficiency and identify a viable alternative to the high-global warming potential (GWP) refrigerant R134a. Conventional exergy analysis reveals that the electronic expansion valve minimizes exergy destruction across all alternative refrigerants compared to both a capillary tube and a thermostatic valve. Further insights are gained through advanced analysis, indicating that the R1234yf system exhibits 3.53 % lower exergy destruction than the R134a system. Notably, the evaporator emerges as the most sensitive component across all refrigerants, contributing the highest average exergy loss (0.88 kW) which can be substantially reduced to 0.67 kW (23.57 %) through pressure ratio optimization. These findings strongly suggest that the low-GWP refrigerant R1234yf presents the most promising alternative to R134a, offering both improved efficiency and reduced environmental impact.